Suitable Electrode Choice for Robotic-Assisted Cochlear Implant Surgery: A Systematic Literature Review of Manual Electrode Insertion Adverse Events - Van de Heyning, Paul; Roland, Peter; Lassaletta, Luis; Agrawal, Sumit; Atlas, Marcus; Baumgartner, Wolf-Dieter; Brown, Kevin; Caversaccio, Marco; Dazert, Stefan; Gstoettner, Wolfgang; Hagen, Rudolf; Hagr, Abdulrahman; et al. (Frontiers in Surgery, 2022)
BACKGROUND AND OBJECTIVE: The Cochlear implant (CI) electrode insertion process is a key step in CI surgery. One of the aims of advances in robotic assisted CI surgery (RACIS) is to realize better cochlear structure preservation and to precisely control insertion. The aim of this literature review is to gain insight on electrode selection for RACIS by acquiring a thorough knowledge on electrode insertion and related complications from the classic CI surgery involving a manual electrode insertion process. METHODS: A Systematic electronic search of the literature was carried out using PubMed, Scopus, Cochrane, and Web of Science to find relevant literature on electrode tip fold over (ETFO), electrode scalar deviation (ESD), and electrode migration (EM) from both pre-shaped and straight electrode types. RESULTS: A total of 83 studies including 8675 ears implanted with CI comprising pre-shaped (4941) and straight electrodes (3734) were evaluated. The rate of ETFO (26 studies, 2407 ears), ESD (39 studies, 3073 ears), and EM (18 studies, 3195 ears) was determined. An incidence rate (± 95% CI) of 5.3% (4.4% - 6.6%) of ETFO, 28.6% (26.6% - 30.6%) of ESD, and 0.53% (0.2% - 1.1%) of EM is associated with pre-shaped electrodes, whereas with straight electrodes it was 0.51% (0.1% - 1.3%), 11% (9.2% - 13.0%) and 3.2% (2.5% - 3.95%) respectively. The differences in proportion between the pre-shaped and straight electrode types are highly significant (p < 0.001). Laboratory experiments show evidence that robotic insertions of electrodes are less traumatic than manual insertions. CONCLUSION: Considering the current electrode designs available and the reported incidence of insertion complications, the use of straight electrodes in RACIS as well as manual insertion appears to be less traumatic to intracochlear structures compared to pre-shaped electrodes. However, EM of straight electrodes should be anticipated. RACIS has the potential to reduce these complications.